Effectiveness cognitive behavioral therapy in reducing psychological stress and increasing medication compliance in pulmonary tuberculosis patients: A systematic review - Tety Nikasia Matanari; Etty Rekawati; Astuti Yuni Nursasi; Henny Permatasari (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Tuberculosis not only affects the physical condition of sufferers but also causes psychological problems such as anxiety and depression in tuberculosis patients. These psychological disorders will have an impact on treatment that is still undergoing treatment. The efforts that can be given are non-pharmacological therapy, namely Cognitive Behavioral Therapy (CBT), this therapy is carried out by changing the wrong way of thinking about the disease experienced by the patient. Purpose: To determine the effectiveness of Cognitive Behavioral Therapy (CBT) in reducing psychological stress and increasing medication compliance in pulmonary tuberculosis patients. Method: A systematic review with article selection guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The systematic review process begins with the formulation of clinical questions relevant to the topic. Before this, the authors establish PICOS criteria, which stand for: P (problem, patient, or population), I (intervention, prognostic factor, or exposure), C (comparison or control), O (outcome), and S (study design). For this article, P: Patients diagnosed with pulmonary tuberculosis who experience psychological stress, I: Cognitive Behavioral Therapy (CBT), C: Standard care or conventional treatment without CBT, O: Reduction in psychological stress (levels of stress, anxiety, or depression), S: Randomized Controlled Trials. The article search was conducted systematically using the keywords: "Tuberculosis" AND "Cognitive Behavioral Therapy” AND “Cognitive Therapy” AND “Medication Adherence” AND “Medication Compliance” AND “Psychological“AND “Depression” AND “Anxiety”. Results: This study shows that Cognitive Behavioral Therapy (CBT) is effective in reducing psychological stress and increasing medication compliance in pulmonary tuberculosis patients. Conclusion: CBT is effective in increasing medication adherence in pulmonary tuberculosis patients.